Islamic Boarding School Strategy for Enhancing Comunity Religious Beliefs Through One House One Student System - Alvin Dian Pramuja; Zainul Arifin (Yayasan Letiges Konsultan Sosial, 2024)
This research aims to explore more deeply the strategy of strengthening the religiosity of the Wonocepokoayu Village community through the one house one student system initiated by Islamic Boarding House Mambaul Hikam Lumajang. The approach used in this research is a qualitative approach with descriptive methods. This research involved 7 (seven) participants consisting of Foundation administrators, managers, and public relations of the Mambaul Hikam Islamic Boarding School, as well as devices and alumni of the Islamic boarding school in Wonocepokoayu village who potentially know the one house one student system. The results show that the one house one student strategy is not only a solution to improve religion through education but also creates synergy between various elements of society in supporting the formation of religious characters at the local level. With this program, Wonocepokoayu Village is expected to achieve positive changes in its religious dimension for the better.